Journal of Enzymes for a New Applicable Knowledge - Marcolongo Loredana (Journal of Enzymes, 2018)
This editorial frames the journal’s mission to spotlight enzyme research with clear application pathways. It invites submissions on biocatalysis, diagnostics, and therapeutics, emphasizing reproducibility and real‑world impact.